ROS-GC interlocked Ca2+-sensor S100B protein signaling in cone photoreceptors: review - Sharma, Rameshwar K.; Makino, Clint L.; Hicks, David; Duda, Teresa (Frontiers in Molecular Neuroscience, 2014)
Photoreceptor rod outer segment membrane guanylate cyclase (ROS-GC) is central to visual transduction; it generates cyclic GMP, the second messenger of the photon signal. Photoexcited rhodopsin initiates a biochemical cascade that leads to a drop in the intracellular level of cyclic GMP and closure of cyclic nucleotide gated (CNG) ion channels. Recovery of the photoresponse requires resynthesis of cyclic GMP, typically by a pair of ROS-GCs, 1 and 2. In rods, ROS-GCs exist as complexes with GCAPs, which are Ca2+-sensing elements. There is a light-induced fall in intracellular Ca2+. As Ca2+ dissociates from GCAPs in the 20 to 200 nM range, ROS-GC activity rises to quicken the photoresponse recovery. GCAPs then progressively turn down ROS-GC activity as Ca2+ and cyclic GMP levels return to baseline. To date, GCAPs mediate the only known mechanism of ROS-GC regulation in the photoreceptors. However, in mammalian cone outer segments, cone synapses and ON bipolar cells, another Ca2+ sensor protein, S100B, complexes with ROS-GC1 and senses the Ca2+ signal with a K1/2 of 400 nM. Unlike GCAPs, S100B stimulates ROS-GC activity when Ca2+ is bound. Thus, the ROS-GC system in cones functions as a Ca2+ bimodal switch; with rising intracellular Ca2+, its activity is first turned down by GCAPs and then turned up by S100B. This presentation provides a historical perspective on the role of S100B in the photoreceptors, offers a pictorial model for the “bimodal” operation of the ROS-GC switch and projects future tasks that are needed to understand its operation. Some accounts of this review have been adopted from the original publications of these authors.